2010
DOI: 10.1017/s0007114510000504
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pomegranate seed oil on hyperlipidaemic subjects: a double-blind placebo-controlled clinical trial

Abstract: In vitro and in vivo studies have shown that punicic acid, a type of conjugated fatty acid and the main constituent of pomegranate seed oil (PSO), has anti-atherogenic effects. The present study aimed at determining the effect of PSO treatment on serum lipid profiles. This double-blind placebo-controlled randomised clinical trial included fifty-one hyperlipidaemic subjects, diagnosed according to National Cholesterol Education Program definition, and randomly assigned to the PSO and the control groups. The PSO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(74 citation statements)
references
References 28 publications
4
68
1
1
Order By: Relevance
“…The main constituents of pomegranate seed oil (PSO) are conjugated fatty acids, including oleic, linoleic, palmitic, punic and stearic acids, which have an important role in preventing cardiovascular diseases, by reducing cholesterol levels and promoting an anti-atherogenic effect (Schubert et al 1999;Mirmiran et al 2010). The phenolic and flavonoid contents might contribute to the PSO antioxidant activity, by eliminating free radicals and decreasing oxidative stress and lipid peroxidation, which plays an important role in the prevention and treatment of cancer (Poulsen et al 1998;Schubert et al 1999).…”
Section: Research Articlementioning
confidence: 99%
“…The main constituents of pomegranate seed oil (PSO) are conjugated fatty acids, including oleic, linoleic, palmitic, punic and stearic acids, which have an important role in preventing cardiovascular diseases, by reducing cholesterol levels and promoting an anti-atherogenic effect (Schubert et al 1999;Mirmiran et al 2010). The phenolic and flavonoid contents might contribute to the PSO antioxidant activity, by eliminating free radicals and decreasing oxidative stress and lipid peroxidation, which plays an important role in the prevention and treatment of cancer (Poulsen et al 1998;Schubert et al 1999).…”
Section: Research Articlementioning
confidence: 99%
“…Also, the results showed a diminution of cholesterol HDL-C ratio while, the serum cholesterol, LDL cholesterol remained unchanged. Therefore, this study could demonstrate a beneficial effect of lipid profile including TAG and TAG:HDL-C ratio 52 . This study showed that weight gain was associated with an increase in biomarkers of cholesterol profile, adipose tissue accumulation (P<0·05).…”
Section: Effects On Lipid Profilementioning
confidence: 76%
“…Antioxidant and antiinflammatory activities are the main features of PSO which results from inhibition of lipid peroxidation and neutrophil-activation 37,39,51 . Effects of PSO on body weight and serum lipid profile are inconsistent and many studies confirmed weight reducing effects but the effects of PSO on reducing in serum triglyceride, phospholipid, cholesterol, and LDL-cholesterol levels are contradictory 40,52 . PSO reduces body weight, leptin and insulin levels, enhances glucose tolerance, improves peripheral insulin sensitivity, increases carbohydrate oxidative capacity, and inhibits the progression of type2 diabetes 31,53 .…”
Section: Pharmacological Actions Of Psomentioning
confidence: 99%
See 1 more Smart Citation
“…They also showed no beneficial correlation between PSO consumption and insulin profiles [44] . Moreover, PSO was demonstrated to have an antioxidant activity and useful effects on lipid profile of dyslipidemic patients [25,45] . Arao et al demonstrated that feeding of obese Otsuka LongEvans Tokushima fatty (OLETF) rats with dietary 1% PSO did not affect abdominal adipose tissue weights or blood lipid levels when compared to the normal diet group.…”
Section: Pa and Diabetes Mellitusmentioning
confidence: 99%